What power shift to China? - Guy De Jonquières (European Centre for International Political Economy (ECIPE), 2012)
As the west struggles under the double burden of anaemic growth and massive debt, the belief has become common that power is shifting to China. But while western influence in the world may be diminishing, it is by no means certain that China possesses either the will or the capacity to shape tomorrow's international order to its own design and to impose its writ on other nations. In a new policy brief Guy de Jonquières claims that although western disarray has embolden China to assert its interests and resist external pressures more robustly, it shows little sign of having any coherent global agenda, beyond demanding international respect and securing its own material prosperity.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Internationale Wirtschaft; China